[Crowd sitting in front of the completed Kennedy Library] - P. K. Phillips::::::photographer::: (1981)
Dedication of library under the name of Robert E. Kennedy. A crowd of people is sitting in front of the entrance to the newly completed library. Some of the people pictured are as followed: President Warren Baker, Dale Andrews, and the director of the library, Walsh.